Education Quality Improvement Through School Based Management - Imam Tabroni; Rini Purnama Sari; Ummu Salamah; Sri Mulyani (Jurnal Multidisiplin Madani, 2022)
School-Based Management (SBM) is an attempt to improve the quality of education. This study aims to determine the process of preparation, planning, implementation, management and community participation as well as the factors supporting the achievement of integrated education. The method used in this study is a descriptive method with a qualitative approach. Data collection techniques through observation and interviews. The subjects of this study were principals and teachers of the Cijantung Sukatani State Elementary School, Purwakarta. The results showed that the planning process in the implementation of School-Based Management (SBM) which includes the establishment of the School's Vision and Mission as well as the discipline carried out by every school member. The implementation of School-Based Management (SBM) at SD Negeri Cijantung is planned and can be implemented properly.